St. James's Place Wealth Management Tax Guide 2009-2010 - Sinclair, Walter; Lipkin, Barry (Palgrave Macmillan UK, 2009)
The 38th annual edition of the leading guide to taxation in Britain. This practical and user-friendly guide is a bestseller with students, professionals, accountants and private individuals, explaining in simple terms how the UK tax system works and how best to minimise tax liabilities